Nutritive Value of Fermented Water Hyacinth (Eichornia crassipes) Leaf with Aspergillus niger in Tegal Duck - Mangisah, I; Wahyuni, HI; Tristiarti, Tristiarti; Sumarsih, S; Setyaningrum, S (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2010)
Two steps of experiment were conducted to evaluate the proximate composition and nutritive value of fermented water hyacinth leaf (WHL) with Aspergillus niger in Tegal duck. Twenty two heads of eight-week Tegal ducks with an average body weight of 1202.55 + 111.14 g were used in this experiment. There were two treatments namely: non-fermented (NFWH) and fermented with Aspergillus niger (FWHAN). Each treatment was replicated 10 times. Data gathered were analyzed using t-student test. The proximate composition between NFWH and FWHAN showed an increase in crude protein/CP (11.44 vs 16.09%) and ash (12.76 vs 22.37%) but a decrease in crude fiber/CF (21.51 vs 16.62%) and nitrogen free extract/NFE (53.20 vs 43.59%). The nutritive value of diet for eight-week Tegal ducks showed that fermentation of WHL with Aspergillus niger significantly increased CP digestibility, true metabolizable energy (TME) and nitrogen retention (NR), but not for CF digestibility. It could be concluded that fermentation of WHL with Aspergillus niger increases the nutrient quality and the nutritive value of diet for eight-week Tegal ducks in term of CP digestibility, TME and NR. (Animal Production 12(2): 100-104 (2010)Key Words: water hyacinth leaf, fermentation, Aspergillus niger, biological value, Tegal ducks